Precise Assessment on Birth Information at the Civil Registry and Live Births Information System in Minas Gerais, Brazil - Horta,Cláudia Júlia Guimarães (2018)
Abstract Objective: to assess the precision on birth information at the Civil Registry and Sistema de Informações Sobre Nascidos Vivos (Sinasc) (Live Births Information System) in Minas Gerais with the purpose to analyze the most recent fecundity level and pattern on women and to assess the hypotheses on the fertility component for populational projections adopted by the Instituto Brasileiro de Geografia e Estatística (IBGE) (Brazilian Institute of Geography and Statistics) in the 2013 review. Methods: the estimation level of under registration at the Civil Registry and Sinasc was based on the comparison of number of births registered by these sources with the number of births obtained from an independent source, estimated by the Brass P/F technique with adaptation. Results: in 2010, the coverage on the Civil Registry and Sinasc was 96.0% and 95.0%, respectively. In the period of 2003 to 2015, both sources point to the same trend. From 2011, the total number of births was practically the same. The corrected Total Fertility Rate and The Specific Fertility Rates had a very similar level and pattern in the period of 2010 to 2015. Discrepancies in the fertility hypotheses were observed from the IBGE. Conclusions: from 2010, the births registered in both data sources were considered as good statistical quality in Minas Gerais and the hypotheses of the fertility level and pattern in the IBGE projections need to be revised.